2019
DOI: 10.1055/a-0994-4361
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of over-the-scope clips for gastrointestinal bleeding: a systematic review and meta-analysis

Abstract: Background The over-the-scope clip (OTSC) has been increasingly utilized for the management of gastrointestinal (GI) bleeding. Limited efficacy data are currently available from large-scale studies. Methods An electronic database search was conducted for eligible articles using OTSCs for hemostasis in GI bleeding. The primary outcome was the rate of definitive hemostasis after primary hemostasis and without rebleeding at follow-up. Secondary outcomes were: primary technical success, primary clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 33 publications
4
22
1
Order By: Relevance
“…In a systematic review and meta-analysis, Chandrasekar et al examined the effectiveness of cap-mounted clip technology in achieving "definitive hemostasis" in GI bleeding, defined as successful primary hemostasis without rebleeding during the follow-up period (median 56 days) [138]. This meta-analysis included 21 studies (1 RCT, 20 observational) with 851 patients (687 with UGIH).…”
Section: Performance Of Upper Gi Endoscopymentioning
confidence: 99%
“…In a systematic review and meta-analysis, Chandrasekar et al examined the effectiveness of cap-mounted clip technology in achieving "definitive hemostasis" in GI bleeding, defined as successful primary hemostasis without rebleeding during the follow-up period (median 56 days) [138]. This meta-analysis included 21 studies (1 RCT, 20 observational) with 851 patients (687 with UGIH).…”
Section: Performance Of Upper Gi Endoscopymentioning
confidence: 99%
“…In conclusion, it has been shown that the OTSC is a safe hemostatic tool [1,2]; however, our case shows that precise E-Videos Video 1 Duodenal ulcer that was re-bleeding from under the clip base after application of a 11/3 traumatic over-the-scope clip (OTSC). An endoloop was applied as endoscopic rescue therapy when the OTSC failed to control bleeding.…”
mentioning
confidence: 67%
“…Rebleeding was seen in 10.3% of patients. The failure rate of OTSCs was 9% when used as primary therapy and 26% when used as rescue/salvage therapy [ 17 ]. The data are limited regarding the use of OTSC as a primary therapy [ 4 ].…”
Section: Discussionmentioning
confidence: 99%